The role of appearance schematicity in the internalization of media appearance ideals: A panel study of preadolescents. (24th July 2017) - Rousseau, Ann; Gamble, Hilary; Eggermont, Steven
ABSTRACT: Individuals who are more strongly invested in their appearance, appearance schematics, have a tendency to engage in appearance‐related comparison. Appearance schematicity consists of two components. The self‐evaluative component concerns the degree to which appearance is central to self‐worth, referred to as dysfunctional appearance beliefs. Motivational salience refers to the engagement in behaviors designed to enhance appearance, such as body surveillance. Based on a three‐wave panel survey of 973 Flemish preadolescents ( M age = 11.15, SD = 1.13) we found that the motivational and self‐evaluative components had a different impact on media internalization. For preadolescents who engaged in more body surveillance, watching television resulted in more media internalization. For preadolescents who had fewer dysfunctional appearance beliefs, watching television resulted in more media internalization. These findings suggest that appearance schematicity is an important susceptibility variable in the relationship between TV‐exposure and media internalization, and emphasize the importance of investigating individual dispositions beyond gender differences.